Hasil Kinerja Karyawan Berpengaruh Terhadap Komitmen Dan Sikap Kerja Karyawan (Study Kasus Di PT Metriko Palembang) - Sudarna; Tutik Pebrianti; Imam Suroso; Aras Tulip (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2018)
After the employee’s problem inventoried at PT. Metriko, the problems were certainly raised not only from the working environment, with the co-workers, superiors or with the load of work itself. Employee’s attitude is represented with satisfaction and working involvement. This attitude certainly will have an impact and or influence towards the employee’s performance. The purpose of this research is to analyse if a commitment and a employee’s attitude caused an impact towards the employee’s performance. Based on calculation analysed by using simple linear regression with SPSS ver. 22.00, the results are: Satisfaction Coefficient B = 1,541 with p value = 0,000 < 0,05 with determination R2–0,421 (4,21%); Management Commitment Coefficient B = 0,784 with p value 0,000 < 0,05 with determination R2= 0,413 (41,3%); and Employee’s attitude Coefficient B = 1,809 with p value 0,000 < 0,05 with determination R2–0,433 (43,3%). It can be concluded that the hypotheses stated that commitment and employee’s attitude have a positive relation and significant impact towards the employee’s performance.